Prospective Longitudinal Patient-Reported Satisfaction and Health-Related Quality of Life following DIEP Flap Breast Reconstruction: Relationship with Body Mass Index. Issue 6 (June 2019) - Ochoa, Oscar; Garza, Ramon; Pisano, Steven; Chrysopoulo, Minas; Ledoux, Peter; Arishita, Gary; Ketchum, Norma; Michalek, Joel E.; Nastala, Chet
Abstract : Background: Breast reconstruction plays a significant role in breast cancer treatment recovery. Introduction of the BREAST-Q questionnaire has facilitated quantifying patient-reported quality-of-life measures, promoting improved evidence-based clinical practice. Information regarding the effects of body mass index on patient-reported outcomes and health-related quality of life is significantly lacking. Methods: Consecutive deep inferior epigastric perforator (DIEP) flap breast reconstruction patients prospectively completed BREAST-Q questionnaires preoperatively and at two points postoperatively. The first (postoperative time point A) and second (postoperative time point B) postoperative questionnaires were completed 1 month postoperatively and following breast revision, respectively. Postoperative flap and donor-site complications were recorded prospectively. BREAST-Q scores were compared at all time points and stratified by body mass index group (⩽25, >25 to 29.9, 30 to 34.9, and ≥35 kg/m 2 ). Results: Between July of 2012 and August of 2016, 73 patients underwent 130 DIEP flap breast reconstructions. Breast satisfaction and psychosocial and sexual well-being scores increased significantly postoperatively. Chest and abdominal physical well-being scores returned to baseline levels by postoperative point B. Preoperatively, stratified by body mass index, breast satisfaction and psychosocial well-being scores were significantly lower among patients with body mass index of 35 or higher and of more than 30, respectively. After reconstruction, not only were breast satisfaction, psychosocial, and sexual well-being scores significantly improved in all body mass index groups versus baseline, but also between–body mass index group differences were no longer present. Outcome satisfaction, flap, and donor-site morbidity were similar irrespective of body mass index. Conclusions: Patient-reported outcomes demonstrate significant improvements in breast satisfaction and psychosocial and sexual well-being among patients following DIEP flap reconstruction. Preoperative differences in quality-of-life scores were improved in patients with obesity (body mass index ≥30 kg/m 2 ). CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II. Abstract : Evidence-Based Outcomes Article.